Educación Financiera en los Habitantes de la Parroquia Chuquiribamba - Chamba Ortega, Erika Thalia (2023)
Financial education is a process of instruction aimed at developing an understanding of economic concepts and the understanding of abilities that facilitate informed and thoughtful financial decision-making. In this context, the objective of this research focuses on analyzing the level of financial education of the inhabitants of the Chuquiribamba parish; the study begins with the collection of data through a survey adapted to the methodology of the Organization for Economic Cooperation and Development and the International Network of Financial Education proposed by Atkinson, and Messy applied to 267 inhabitants between the ages of 20 and 60 years, in which we used Microsoft Excel and the PSPP program for the analysis and processing of the data and thus to determine the level of knowledge in financial education that the inhabitants possess. Therefore, it is evident that the inhabitants lack knowledge of basic financial and economic concepts, limited access to financial products and services and budgeting, which leads to poor management of economic resources; likewise, they do not have the habit of saving since they do not receive a fixed monthly income. Because of this situation, we developed a training program to contribute to the educational development and the importance of the application of financial education in people, focusing on basic concepts of financial education, financial system, savings, budget and investment, credit and economic terms concerning finances; we trained 72% of the population, achieving that the inhabitants are located in the middle level in greater concentration and improving their skills by encouraging them to practice the habit of saving to make informed financial decisions to maintain a financial and economic balance.